STRATEGI PENGEMBANGAN AGROWISATA DI DESA WISATA CIBODAS KECAMATAN LEMBANG, KABUPATEN BANDUNG BARAT - Endah Djuwendah; Rayhan Ahmad Giffary (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Cibodas Village is one of the agro-tourism areas in West Bandung Regency which is a tourist village managed by local communities. Agrotourism management in Cibodas Village still looks underdeveloped, so a development strategy needs to be carried out with the aim that the potential can continue to be explored and improved. The purpose of this study is to analyze the position of the agro-tourism business in Cibodas Lembang Village, and to find out what strategies can be applied in the development of agro-tourism in Cibodas Lembang Village. This study uses a qualitative design with a case study approach. Analysis of the data used using SWOT analysis and ANP (Analytical Network Process). The results of the ANP analysis show that the main priority alternative strategy in developing agro-tourism in Cibodas Village is a strategy to promote more aggressively with various institutions regarding tourist villages that have a unique agro-education concept.